PLACE IDEA FOR AGING CARE: DETACHED HOUSE WELL-BEING - Xian, Gabriela Emilly; Defiana, Ima (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2023)
As the world's population is getting older, the condition of elderly experience mobility limitations, sensory impairments, and cognitive decline. There is an increasing need to address the elderly’s health and life quality. Concurrently, biophilic design has gained recognition as a promising approach to enhance human health and well-being by incorporating natural elements into the built environment. Integrating place identity and place attachment principles into the early stages of planning and construction can optimize the benefits for elderly residents. The research’s purpose is to find how the place attachment could help to improve the well-beingness of elderly. This research examines the cases of detached house with field studies and analyses it from the principle of place identity and the dimension of place attachment to make an adaptation also modifications to accommodate specific needs. The resulting concept is the use of vegetation, the dynamics of wall textures and colours, furniture, railings, and Chinese geometry for creating age-friendly and sustainable environments.